Importance of plasmonic scattering for an optimal enhancement of vibrational absorption in SEIRA with linear metallic antennas - Neumann, Tomasz; Huck, Christian; Vogt, Jochen; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
Surface-enhanced infrared absorption (SEIRA) and surface-enhanced Raman scattering (SERS) represent very effective techniques to detect molecular vibrational fingerprints. These techniques can be improved thanks to the use of plasmonic antennas that produce strong resonant near-fields in their vicinity, enhancing the signal of vibrational samples. Here we study the role of plasmonic absorption and scattering of the hosting antennas in the resulting SEIRA signal. Using numerical simulations of the antenna-sample infrared response, we show that the optimal SEIRA signal measured in transmittance (as extinction) is achieved when the spectral maxima of absorption and scattering of the antennas are of similar magnitude. Paradoxically, when the optimal condition for SEIRA is fulfilled, the decomposition of the signal into the contribution from scattering and from absorption show that the vibrational fingerprint is exclusively a result of the scattering, with no contribution from absorption. Using a simple analytical model for the description of the fundamental resonance of linear nanoantennas made of a Drude-type metal, we provide guidelines for controlling the plasmonic light scattering and light absorption properties, thus showing how the optimal condition for SEIRA can be achieved in practical situations.